Quality in academic postgraduate studies: design and validation of an evaluation instrument - Ramos Azcuy, Fridel Julio (2024)
The self-assessment of master's programs taught totally or partially in virtual environments allows their improvement and favors evidence-based decision making. The effectiveness of self-assessment depends on the indicators used, so it is essential to determine their value. The objective of the work was to implement an instrument for evaluating indicators for self-assessment of the quality of virtual master's programs. The identification and analysis of scientific articles, design guides and technical standards that address the evaluation of indicators was carried out. The Google and Google Scholar search engines were used with the keywords: indicators, indicator systems, indicator evaluation. As a result of the analysis, six quality criteria were identified for the indicators used in the self-assessment of the virtual master's programs. An instrument was developed to measure these six criteria using a five-level Likert scale. The pilot test of the designed instrument allowed its validation and improvement of the indicators used in the self-assessment of the virtual master's programs in the Chair of Quality, Metrology and Standardization of the University of Havana.